Functional Characterization of Yiro10w (DSN1) and Yor228c Genes in Saccharomyces Cerevisiae - Yiap, Beow Chin (2004)
The aim of this project was to functionally decipher two novel genes of Saccharomyces cerevisiae (YOR228C and YIROIOW). Four levels of study were undertaken to achieve the aims of this study including bioinformatics data mining and prediction, gene deletion study, phenotypic analysis and protein profiling. Sequence analysis of YOR228C predicted the expression of a 34 kDa transmembrane protein of low abundance with the potential of forming a homodimer. It could be a stress-responsive gene that also regulates cell growth in yeast but it was not an essential component of the cell. On the other hand, Yir010wp has a size of 66 kDa and would be a heterodimer in a complex. This low abundant protein may be related to cell division cycle as it was found to be incorporated within the yeast spindle pole body. The necessity for its exact stoichiometry was a sign of gene dosage sensitivity as demonstrated by the reduction in heterologous fitness. Deletion of a single copy of YIROIOW caused chromosomal segregation error leading to aneuploidy. Furthermore, double knockout of the gene from the genome was lethal, implying its essentiality to the yeast cell. As a whole, this study has successfully elucidated the general functions of the two genes under investigation, namely the relationship between YOR228C to growthlstressresponse and the link between YIROIOW to the cell division cycle.